Flood study of Nam Pong river at Pong Neeb gorge - Khanate Sakulyong; Nielsen, Steen Asger; Tawatchai Tingsanchali; Bogardi, Janos J.; The Australian Government (Bangkok : Asian Institute of Technology, 1986)
The main objective of this study was to verify to what extent heavy deforestation within Nam Pong river basin during the recent decades or retention of the Pong Neeb gorge explains the changes in the observed floods of the basin. The deforestation effect was detected by statistical analysis on annual maximum runoff data from Yorn, Nan and Pasak river basins, where extensive forest destruction has taken place. Results of the study show, that the three basins have no any significant systematic changes on the flood peaks. This indicates that for big basins with gradual deforestation over a number of years the long-tenn effect of deforestation on the flood peaks is so small that it has no practical impact, particularly when compared to the natural climatic variations. The mathematical m:xlel, a combination of hydrological storage routing and hydrodynamic river routing, was developed to simulate the flood flows of Nam Pong river including the retention storage upstream of the gorge in pre-dam period and to verify the effect of the retention on flood peaks. The hydrological storage routing was based on the continuity equation for a single reservoir. The hydrodynamic river routing consists of the unsteady free surface flow equations which were solved numerically by using the finite difference approximation of the implicit scheme. The various flood inf low hydrographs to Ubol Ratana reservoir were used as the input of the combined m:xlel. Results of this simulation show, that the peak discharges downstream of the gorge were reduced considerably by the effect of the retention storage. The peaks were reduced by 35% upto 63% for a 2-yr flood and a 10,000-yr flood respectively. The Manning's roughness coefficient was also considered to be a factor affecting the flood flow in the river channel downstream of t he gorge. However, the changes of flood flow influenced by the value of Manning's roughness coefficient was insignificant compared to the peak reductions affected by the retention storage of the gorge.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Floods -- Nam Pong River